2014
DOI: 10.1177/1471301214539691
|View full text |Cite
|
Sign up to set email alerts
|

Trends in referred patient profiles in a memory clinic over 20 years

Abstract: The increasing numbers of people with dementia in the UK, as well as the associated costs have led to an effort to improve dementia services for the benefit of patients, caregivers and the taxpayer. These efforts have frequently emphasised the importance of early diagnosis in dementia care. We sought to test the hypotheses that the mean cognitive score of new referrals to a secondary care memory assessment service increased while mean age decreased over a period of 20 years. We retrospectively analysed the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In our study, we also observed a shift towards an upturn in day clinic visits over the years. A similar pattern was observed in a study by Azam et al 23 This study additionally revealed a significant increase in mean cognitive scores of referrals to secondary care memory clinics over a 20-year period, probably due to increased awareness. This means that patients are referred in less-advanced stages of the disease.…”
Section: Readmission Risksupporting
confidence: 89%
“…In our study, we also observed a shift towards an upturn in day clinic visits over the years. A similar pattern was observed in a study by Azam et al 23 This study additionally revealed a significant increase in mean cognitive scores of referrals to secondary care memory clinics over a 20-year period, probably due to increased awareness. This means that patients are referred in less-advanced stages of the disease.…”
Section: Readmission Risksupporting
confidence: 89%
“…That is why we think that only immunovirologically controlled PLHIVs with plVL <50 copies/mL can serve to optimally evaluate the true brain consequences of chronic HIV infection. Moreover, cognitive decline should not be evaluated with HAND criteria but rather with defined neuropsychological norms, as widely acknowledged by neurocognitive specialists who use them in memory clinics (Azam et al 2016). To date, none of the numerous VCI criteria has been validated for PLHIVs or may be preferentially chosen.…”
Section: Discussionmentioning
confidence: 99%
“…The main stumbling block of the Frascati criteria [21] is that they label > 30% of a normative reference population as cognitively impaired, which yields an unreasonably high false-positive proportion of cognitively impaired participants in a study population, due to their lower-than-expected specificity [19,[22][23][24][25]. Because evidence is mounting in support of not using the HAND criteria in the modern cART era in resource-rich settings and the availability of updated standards, we chose to apply the validated, normative datasets threshold of impairment, as widely acknowledged in memory clinics [26]. Raw scores for each cognitive domain test, except the 9-hole peg test, were normalized to age, sex, and educational levels, yielding z scores for analyses.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%